The rise and fall of organized crime in the United States - Jacobs, James B. (Crime and justice, 2020)
The Italian American Cosa Nostra crime families are the longest-lived and most successful organized crime organizations in US history, achieving their pinnacle of power in the 1970s and 1980s. The families seized opportunities during the early twentieth-century labor wars and under national alcohol prohibition from 1919 to 1933. Control of labor unions gave them power to determine the companies that could operate in various sectors and enabled them to establish employer cartels that rigged bids and fixed prices, and provided opportunity to exploit pension and welfare funds. The racketeers were urban power brokers. The families also profited from gambling, illicit drugs, loan-sharking, prostitution, and pornography, and they extorted protection payments from other black marketeers. For decades they faced little risk from law enforcement. FBI Director Hoover denied the existence of a national organized crime threat. Local police were corrupted. After Hoover’s death, the FBI made eradicating organized crime a top priority. Relentless law enforcement coincided with socioeconomic and political changes that greatly weakened the Cosa Nostra families.